Training in Arabic Grammar (Nahwu): Building Foundations to Mastery - Hamdy, Mohammad Zainal; Ningsih, Wiwik Prasetiyo (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2025)
The mastery of nahwu (Arabic grammar) remains one of the most persistent challenges for students in Islamic schools, despite their strong interest in the subject. At Madrasah Miftahul Ulum Angsokah Timur, many students expressed enthusiasm for learning nahwu, yet they often faced difficulties due to limited study time, fragmented focus on other subjects, and insufficient teaching methods and media used by teachers. This study aims to address these challenges by designing and implementing an intensive nahwu training program for beginner and intermediate students during the twelve-day Maulid holiday. The research employed a qualitative descriptive approach with field observation, interviews, and documentation as the main data collection techniques. The training was conducted three times daily—after dawn, afternoon, and evening prayers—using Talkhīs al-Nahw for beginners and Matn al-Ājurrūmiyyah for intermediate learners. Various interactive methods were applied, including question-and-answer sessions, role play (masrohiyyah), peer teaching, and group drama competitions, followed by a reading test from al-Taqrīb to evaluate progress. The findings indicate that students showed remarkable enthusiasm and significant improvement in their grammatical understanding and reading ability. Surprisingly, the drama-based activities not only enhanced conceptual comprehension but also fostered motivation and collaborative skills. This study contributes to Arabic pedagogy by demonstrating that short-term intensive training, when combined with participatory methods, can effectively strengthen nahwu competence and serve as a model for other Islamic educational institutions.